Pelecehan Seksual terhadap Korban ditinjau dari Permendikbud Nomor 30 Tahun 2021 - Aulia Virgistasari; Anang Dony Irawan (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
Sexual harassment is an abuse of power from male sexuality, so that harassment can occur because it starts from a position that places the throne of men higher than women, crimes against women often experience unfair treatment and violations of their rights. This sexual crime does not only take place in the private room, the family environment, the playing environment, the office environment, or the company. But it can also happen in a college environment. The formulation of the problem in this paper is first, whether victims of sexual harassment in a university environment can get legal protection. And second, what is the form of legal protection for victims of sexual harassment in universities. The purpose of the study was to find out how the legal protection of victims of sexual harassment in the university environment is and also to analyze the forms of legal protection that are reviewed in Permendikbud Number 30 of 2021. The research method used is normative juridical research. With the presence of Permendikbud Number 30 of 2021, there is no longer any reason for universities not to prevent and handle sexual violence. The reason for the issuance of this regulation is because the cases of sexual harassment in universities are becoming more and more disturbing. If sexual harassment is not prevented then what will be the fate of human civilization, because the source of its civilization itself is not given protection and handling, how can justice be fully served if the victims of these crimes are instead blamed.